TensorFormer: A Tensor-Based Multimodal Transformer for Multimodal Sentiment Analysis and Depression Detection - Sun, Hao; Chen, Yen-Wei; Lin, Lanfen (IEEE transactions on affective computing, 2023)
Sentiment analysis is an important research field aiming to extract and fuse sentimental information from human utterances. Due to the diversity of human sentiment, analyzing from multiple modalities is usually more accurate than from a single modality. To complement the information between related modalities, one effective approach is performing cross-modality interactions. Recently, Transformer-based frameworks have shown a strong ability to capture long-range dependencies, leading to the introduction of several Transformer-based approaches for multimodal processing. However, due to the built-in attention mechanism of the Transformers, only two modalities can be engaged at once. As a result, the complementary information flow in these Transformer-based techniques is partial and constrained. To mitigate this, we propose, TensorFormer, a tensor-based multimodal Transformer framework that takes into account all relevant modalities for interactions. More precisely, we first construct a tensor utilizing the features extracted from each modality, assuming one modality is the target while the remaining tensors serve as the sources. We can generate the corresponding interacted features by calculating source-target attention. This strategy interacts with all involved modalities and generates complementing global information. Experiments on multimodal sentiment analysis benchmark datasets demonstrated the effectiveness of TensorFormer. In addition, we also evaluate TensorFormer in another related area: depression detection and the results reveal significant improvements when compared to other state-of-the-art methods.